Dispersive sensing in hybrid InAs/Al nanowires - Sabonis, Deividas; O'Farrell, Eoin; Razmadze, Davydas; Zanten, David M. T. van; Suter, Judith; Krogstrup, Peter; Marcus, Charles (Applied Physics Letters, 2019)
Dispersive charge sensing is realized in hybrid semiconductor-superconductor nanowires in gate-defined single- and double-island device geometries. Signal-to-noise ratios (SNRs) were measured in both the frequency and time domains. Frequency-domain measurements were carried out as a function of frequency and power and yield a charge sensitivity of 1 × 10–3 e/ Hz for an ∼11 MHz measurement bandwidth. Time-domain measurements yield SNR > 1 for a 20 μs integration time. At zero magnetic field, photon-assisted tunneling was detected dispersively in a double-island geometry, indicating coherent hybridization of the two superconducting islands. At an axial magnetic field of 0.6 T, subgap states are detected dispersively, demonstrating the suitability of the method to sensing in the topological regime.Dispersive charge sensing is realized in hybrid semiconductor-superconductor nanowires in gate-defined single- and double-island device geometries. Signal-to-noise ratios (SNRs) were measured in both the frequency and time domains. Frequency-domain measurements were carried out as a function of frequency and power and yield a charge sensitivity of 1 × 10–3 e/ Hz for an ∼11 MHz measurement bandwidth. Time-domain measurements yield SNR > 1 for a 20 μs integration time. At zero magnetic field, photon-assisted tunneling was detected dispersively in a double-island geometry, indicating coherent hybridization of the two superconducting islands. At an axial magnetic field of 0.6 T, subgap states are detected dispersively, demonstrating the suitability of the method to sensing in the topological regime.